Investigating the possibility of producing animal feed from sugarcane bagasse using oyster mushrooms: A case in rural entrepreneurship - Mojtaba Mahmood Molaei Kermani; Samaneh Bahrololoum; Farzaneh Koohzadi (Journal of Global Entrepreneurship Research, 2019)
Pleurotus florida is an edible mushroom that has commercial potential in the food industry. The objective of this study was to investigate the possibility of producing animal feed from sugarcane bagasse using P. florida. To this aim, sugarcane bagasse was processed with P. florida. The experiment was designed in a completely randomized design with four treatments: processed sugarcane bagasse, raw sugarcane bagasse, wheat straw, and barley straw. This research was carried out under two in vitro and in vivo conditions. In case of in vitro condition, it can be concluded that the amount of dry matter, neutral detergent fiber (P < 0.01), and acidic detergent fiber (P < 0.05) significantly decreased in processed sugarcane bagasse, and the amount of crude protein (P < 0.05), organic matter, and crude ash (P < 0.01) significantly increased. The result of in vivo condition showed that as a result of biological processing of sugarcane bagasse with P. florida, the indices such as digestibility, voluntary feed intake, and relative palatability index increased. The results of this study suggests that treated bagasse could be used as an alternative roughage source for ruminant feeding.
Keywords: 650; Animal feed; Sugarcane bagasse; Oyster mushrooms; Agricultural waste